THE ROLE AND RESPONSIBILITIES OF FOUNDATION BENEFIT OWNERS ARE REVIEWED FROM REGULATION OF THE PRESIDENT OF THE REPUBLIC OF INDONESIA NUMBER 13 OF 2018: PERAN DAN TANGGUNG JAWAB PEMILIK MANFAAT YAYASAN DITINJAU DARI PERATURAN PRESIDEN REPUBLIK INDONESIA NOMOR 13 TAHUN 2018 - Victor Marsangap Nainggolan; Habib Adjie (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
To achieve a guarantee, certainty and legal order, the beneficial owners of the foundation must play a role and be responsible in the form of openness and accountability to the State by carrying out ownership reports. This is a form of implementation Presidential Decree No 13/2018. In addition, to create transparency in the context of preventing and eradicating criminal acts of money laundering and terrorist financing This type of research in legal writing is normative legal research (normative legal research) or doctrinal legal research. The approach method used is a conceptual approach (conceptual approach), namely the study departs from the views and doctrines that have developed in legal science. The role and responsibilities of beneficial owners in foundation legal entities, both when first established and already in operation, are required to comply with the provisions of Presidential Decree No. 13/2018, namely conducting an ownership report. This ownership report needs to be disclosed because there is potential for abuse of power within the foundation. Principles and accountability in foundation management are very necessary to ensure that foundation organs carry out their duties solely to achieve the foundation's social goals and not for other purposes in order to realize good governance within the foundation